APIP's Role in SPIP to Support Defense Force Development - Awan Surya; Mhd. Halkis; Tarsisius Susilo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Law No. 1 of 2004 mandates accountable and transparent management of state finances in Indonesia. To ensure compliance, efficiency, and good governance, the effective implementation of APIP (Aparat Pengawasan Intern Pemerintah or Internal Government Auditors) is crucial. Enhancing the role of APIP is necessary to address the low quality of state financial management, ensure accountability, and support bureaucratic reform for transparent and efficient governance. Purpose: This study aims to analyze the role of APIP within the SPIP (Sistem Pengendalian Intern Pemerintah or Government Internal Control System) framework to support the development of Indonesia's defense forces. The research employs a qualitative descriptive method to explore the role and impact of APIP in state financial management and defense force development. Results: The study reveals a significant improvement in the capabilities of APIP over recent years. In 2015, 85.23% of APIP units were only at capability level 1, which indicates basic operations without full adherence to professional standards. By 2022, 54.74% of APIP units had reached capability levels above 3, indicating compliance with professional standards, enhanced risk management, and improved organizational governance. This increase in capability supports more robust oversight, particularly in the Ministry of Defense and the Indonesian Armed Forces, where APIP plays a vital role in overseeing budget management, the modernization of defense equipment, and the improvement of human resources. Conclusion: While the improvement in APIP capabilities enhances effectiveness, the assessment of efficiency in state financial management remains underemphasized. Addressing this gap is essential for the country's financial reforms aimed at improving public services and ensuring fiscal sustainability. APIP not only maintains integrity, transparency, and accountability but also supports the development of defense forces through comprehensive financial, management, and social audits. The focus on both efficiency and effectiveness is critical to strengthening the relevance of these findings in achieving sustainable governance and defense objectives.